Strontium-lithium mineralized carbon core and method for preparing strontium-lithium mineralized carbon core
The strontium lithium mineralized carbon core prepared through modification treatment and combination molding processes solves the heavy metal problem of mineralized carbon cores in the prior art, improves the precipitation quality and filtration performance of strontium lithium elements, and improves the effluent quality.
Patent Information
- Application Number
- CN202310722251.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2024-12-17
AI Technical Summary
The direct use of natural ore in existing mineralized carbon cores leads to the existence of heavy metal elements such as lead, cadmium, aluminum, etc., which reduces the precipitation quality of mineralized substances and affects user experience.
The modified zeolite powder, dolomite powder, spodumene powder and lithium mica powder are mixed with activated carbon powder in a specific proportion, and the strontium lithium mineralized carbon core is prepared by dry extrusion, dry sintering or wet forming processes. Reduce heavy metal content and improve the precipitation quality of mineralized substances.
The precipitation of strontium and lithium elements in water is improved, the phenomenon of heavy metal exceeding the standard is reduced, the quality of filtered water is improved, and the filtration performance and structural strength of strontium lithium mineralized carbon core is enhanced.
Smart Images

Figure CN119143424A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water purification filter elements, and specifically provides a strontium-lithium mineralized carbon core and a method for preparing the strontium-lithium mineralized carbon core. Background Art
[0002] As people's quality of life improves, their requirements for high-quality drinking water are getting higher and higher. Among them, the post-filter in the water purifier generally uses an activated carbon core to add mineralized substances to improve the taste of the water and increase the mineralized substances that are beneficial to the human body. Among them, trace strontium elements in water can be used to regulate human endocrine, promote the growth of bones and teeth, and prevent osteoporosis. Trace lithium salts can improve learning and memory, and lithium can reduce the risk of patients suffering from dementia.
[0003] The mineralized carbon core in the existing post-filter element uses natural zeolite or natural dolomite to improve the strontium content in the water, and uses natural spodumene and natural lithium mica to improve the lithium content in the water. However, the direct use of the above-mentioned natural ores will inevitably bring other heavy metal elements, such as lead, cadmium, aluminum and other elements that are harmful to human health, which reduces the precipitation quality of mineralized substances in the mineralized carbon core and causes poor user experience.
[0004] Accordingly, the art needs a new strontium-lithium mineralized carbon core to solve the above problems. Summary of the invention
[0005] In order to solve the above problems in the prior art, that is, to solve the problem of poor precipitation quality of the existing mineralized carbon core.
[0006] In a first aspect, the present invention provides a strontium-lithium mineralized carbon core, which includes the following components in parts by weight: 5 to 20 parts of zeolite powder, 5 to 20 parts of dolomite powder, 5 to 30 parts of spodumene powder, 5 to 30 parts of lithium mica powder, 100 to 500 parts of activated carbon powder, and 5 to 40 parts of adhesive.
[0007] In the case of the above-mentioned preferred technical solution of the strontium-lithium mineralized carbon core, the particle size of the activated carbon powder is 80 to 325 meshes.
[0008] In the case of the above-mentioned preferred technical solution of the strontium-lithium mineralized carbon core, the adhesive is polyethylene or acrylic glue.
[0009] In a second aspect, the present invention also provides a method for preparing the strontium lithium mineralized carbon core, which comprises the following steps: an ore processing stage: modifying the natural zeolite, natural dolomite, natural spodumene and natural lithium mica respectively and crushing them to prepare powders for standby use; a mixing stage: mixing the zeolite powder, the dolomite powder, the spodumene powder, the lithium mica powder, the activated carbon powder and the adhesive in proportion and stirring them to obtain a prefabricated mixture; a molding stage: preparing the strontium lithium mineralized carbon core from the prefabricated mixture by any one of dry extrusion, dry sintering or wet molding.
[0010] In the case of the preferred technical scheme of the method for preparing the strontium-lithium mineralized carbon core mentioned above, in the ore processing stage, the specific preparation steps of the zeolite powder or the dolomite powder include: crushing the natural zeolite or the natural dolomite into gravel blocks with a particle size of 1 to 3 cm; washing the natural zeolite or the natural dolomite with clean water and drying it; fumigating and activating the natural zeolite or the natural dolomite with silicon-containing steam; crushing, grinding and sieving the modified natural zeolite or the natural dolomite to obtain the powder for later use.
[0011] In the case of the preferred technical scheme of the method for preparing the strontium-lithium mineralized carbon core described above, in the ore processing stage, the specific preparation steps of the spodumene powder or the lepidolite powder include: crushing the natural spodumene or the natural lepidolite into gravel blocks with a particle size of 1 to 3 cm; washing the natural spodumene or the natural lepidolite with clean water and drying it; calcining the dried natural spodumene or the natural lepidolite at a temperature of 1000 to 1200° C. for 0.5 to 2 hours; crushing, grinding and sieving the calcined natural spodumene or the natural lepidolite to obtain the powder for use.
[0012] In the case of the preferred technical scheme of the method for preparing the strontium-lithium mineralized carbon core mentioned above, the specific processing steps of the activated carbon powder include: placing coconut shell carbon powder in a container and adding a 1% to 3% hydrochloric acid or sulfuric acid solution, and soaking the coconut shell carbon powder in the solution for at least 1 hour; rinsing the coconut shell carbon powder with clean water; and drying and sieving the rinsed coconut shell carbon powder to obtain the activated carbon powder.
[0013] In the case of the preferred technical solution of the method for preparing the strontium-lithium mineralized carbon core described above, the specific steps of the dry extrusion include: filling the prefabricated mixture into an extruder and extruding the prefabricated mixture to form the strontium-lithium mineralized carbon core, and the extrusion temperature of the extruder is 115-200°C.
[0014] In the case of the preferred technical scheme of the method for preparing the strontium-lithium mineralized carbon core mentioned above, the specific steps of the dry sintering include: filling the prefabricated mixture into a mold and compacting it to form a prefabricated carbon core; sending the mold with the prefabricated carbon core into a tunnel furnace sintering equipment for sintering, the sintering temperature is 150-230°C, and the sintering time is 0.5-2 hours; taking out the mold, cooling and demolding it to prepare the strontium-lithium mineralized carbon core.
[0015] In the case of the preferred technical scheme of the method for preparing the strontium-lithium mineralized carbon core mentioned above, the specific steps of the wet forming include: using a vacuum machine to evacuate the cavity of the mold so that the prefabricated mixture is sucked into the mold to form a prefabricated carbon core; using an oven to dry the prefabricated carbon core to prepare the strontium-lithium mineralized carbon core, the drying temperature is 50-150°C, and the drying time is 1-5 hours.
[0016] It can be understood by those skilled in the art that the strontium lithium mineralized carbon core of the present invention includes the following components by weight: 5-20 parts of zeolite powder, 5-20 parts of dolomite powder, 5-30 parts of spodumene powder, 5-30 parts of lithium mica powder, 100-500 parts of activated carbon powder, and 5-40 parts of adhesive. The steps of preparing the strontium lithium mineralized carbon core include an ore processing stage, a mixing stage, and a molding stage. First, natural zeolite, natural dolomite, natural spodumene, and natural lithium mica are respectively modified and crushed to prepare powders for standby use; secondly, zeolite powder, dolomite powder, spodumene powder, lithium mica powder, activated carbon powder, and adhesive are mixed and stirred in proportion to obtain a prefabricated mixture; finally, the prefabricated mixture is prepared into a strontium lithium mineralized carbon core by any one of dry extrusion, dry sintering, or wet molding. The present invention takes pre-treated zeolite powder, dolomite powder, spodumene powder and lithium mica powder, and then mixes them in different proportions to prepare a strontium-lithium mineralized carbon core. The strontium-lithium mineralized carbon core mineralizes and precipitates a large amount of lithium and strontium in purified water, reduces the phenomenon of excessive heavy metals in water, is more beneficial to human health, and improves the quality of water filtered by the strontium-lithium mineralized carbon core. At the same time, the process for preparing the strontium-lithium mineralized carbon core is diversified, which reduces the preparation threshold of the strontium-lithium mineralized carbon core. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings, in which:
[0018] Figure 1 It is a flow chart of the main steps of the method for preparing the strontium-lithium mineralized carbon core of the present invention;
[0019] Figure 2 is a detailed flow chart of the steps of treating natural zeolite or natural dolomite according to the present invention;
[0020] Figure 3 It is a detailed flow chart of the steps of treating natural spodumene or natural lepidolite according to the present invention;
[0021] Figure 4 It is a detailed step flow chart of the preparation method of the strontium-lithium mineralized carbon core of the present invention. DETAILED DESCRIPTION
[0022] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0023] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments, but the embodiments are not intended to limit the present invention. The experimental methods and test methods in the following embodiments are conventional methods unless otherwise specified; reagents, raw materials and related equipment can all be purchased on the market unless otherwise specified.
[0024] It should be noted that, in the description of the present invention, terms such as "upper", "lower", "inside", "outside", "top", "bottom", "in", "out", etc. indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings. This is only for the convenience of description and does not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it should not be understood as a limitation on the present invention.
[0025] In addition, it should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two components. For those skilled in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0026] like Figure 1 As shown, the strontium lithium mineralized carbon core of the present invention includes the following components by weight: 5-20 parts of zeolite powder, 5-20 parts of dolomite powder, 5-30 parts of spodumene powder, 5-30 parts of lithium mica powder, 100-500 parts of activated carbon powder, and 5-40 parts of adhesive.
[0027] The method for preparing the strontium-lithium mineralized carbon core comprises the following steps:
[0028] S1, ore processing stage: natural zeolite, natural dolomite, natural spodumene and natural lepidolite are modified and crushed to prepare powder for standby use;
[0029] S2, mixing stage: zeolite powder, dolomite powder, spodumene powder, lepidolite powder, activated carbon powder, and adhesive are mixed and stirred in proportion to obtain a prefabricated mixture;
[0030] S3, molding stage: preparing the prefabricated mixture by dry extrusion, dry sintering or wet molding to obtain a strontium-lithium mineralized carbon core.
[0031] It should be noted that the S1 ore processing stage includes two methods for processing natural ore.
[0032] like Figure 2 As shown, in the preferred processing method for zeolite powder or dolomite powder, the specific preparation steps include:
[0033] S110, crushing the natural zeolite or natural dolomite into crushed stone pieces with a particle size of 1 to 3 cm;
[0034] S111. Wash the natural zeolite or natural dolomite with clean water and perform drying treatment;
[0035] S112, using silicon-containing steam to perform fumigation activation modification treatment on natural zeolite or natural dolomite;
[0036] S113, crushing, grinding and sieving the modified natural zeolite or natural dolomite to obtain powder for later use.
[0037] Taking the preparation of zeolite powder as an example, a crusher is used to crush natural zeolite into gravel pieces with a particle size of 1 to 3 cm.
[0038] The crushed gravel is repeatedly rinsed with clean water. When the turbidity of the water used for rinsing the gravel is less than 1, the rinsing of the gravel is stopped. The gravel is placed in a drying box at a temperature of 50 to 90 degrees Celsius and dried for 1 to 5 hours to dry the gravel.
[0039] The dried gravel is placed in a container containing silicate vapor for fumigation activation modification, so that heavy metal elements such as lead, cadmium, and aluminum in the gravel are replaced by silicon elements in the silicate vapor in the form of ion exchange, thereby reducing the content of heavy metal elements such as lead, cadmium, and aluminum in the gravel.
[0040] Finally, the modified gravel is crushed by a crusher, and sieved through a 12-40 mesh sieve to select the activated modified zeolite powder for later use.
[0041] It should be noted that the preparation process of dolomite powder is exactly the same as the above-mentioned preparation process of zeolite powder, so it will not be repeated here.
[0042] like Figure 3 As shown, in the preferred processing method for spodumene powder or lepidolite powder, the specific preparation steps include:
[0043] S120, crushing natural spodumene or natural lepidolite into gravel pieces with a particle size of 1 to 3 cm;
[0044] S121. Wash the natural spodumene or natural lepidolite with clean water and dry it;
[0045] S122, calcining the dried natural spodumene or natural lepidolite at a temperature of 1000-1200° C. for 1-2 hours;
[0046] S123, crushing, grinding and sieving the calcined natural spodumene or natural lepidolite to obtain the powder for later use.
[0047] Taking spodumene powder as an example, a crusher is used to crush natural spodumene into gravel pieces with a particle size of 1 to 3 cm.
[0048] The crushed gravel is repeatedly rinsed with clean water. When the turbidity of the water used for rinsing the gravel is less than 1, the rinsing of the gravel is stopped. The gravel is placed in a drying box at a temperature of 50 to 90 degrees Celsius and dried for 1 to 5 hours to dry the gravel.
[0049] The dried crushed stone is calcined at a temperature of 1000-1200°C for 0.5-2 hours.
[0050] Finally, the calcined crushed stone blocks are crushed with a crusher, and the activated and modified spodumene powder is screened out with a 40-100 mesh sieve for later use.
[0051] It should be noted that the preparation process of lepidolite powder is exactly the same as the above-mentioned spodumene powder preparation process, so it will not be repeated here.
[0052] After the above-mentioned ore treatment, the reserve zeolite powder, dolomite powder, spodumene powder and lithium mica powder are obtained respectively.
[0053] In addition, the activated carbon powder of the present invention can be at least one powder selected from coconut shell charcoal, fruit shell charcoal, coal charcoal, wood charcoal, olive shell charcoal, and bamboo charcoal. Of course, the activated carbon powder is preferably coconut shell charcoal powder, which has extremely strong adsorption performance and high strength.
[0054] The specific processing steps of activated carbon powder include: putting coconut shell carbon powder into a container and adding 1% to 3% hydrochloric acid or sulfuric acid solution, and soaking the coconut shell carbon powder in the solution for at least 1 hour; using clean water to rinse the coconut shell carbon powder; drying and sieving the rinsed coconut shell carbon powder to obtain activated carbon powder.
[0055] Specifically, the coconut shell carbon powder in the solution is stirred evenly in a stirrer and then left to stand for 120 minutes. The coconut shell carbon powder is pickled with hydrochloric acid to remove impurities in the activated carbon powder, thereby improving the purity and surface activity of the coconut shell carbon powder.
[0056] Use clean water to rinse the coconut shell charcoal powder. When the pH value of the water used to rinse the coconut shell charcoal powder is between 6 and 8, and the rinsing water is no longer turbid (no obvious black water), stop rinsing the coconut shell charcoal powder.
[0057] The washed coconut shell carbon powder is dried in a drying box. Specifically, the temperature of the drying box is set to 40 to 100 degrees Celsius, and the drying time is set to 8 to 24 hours to evaporate the clean water adsorbed in the activated carbon powder.
[0058] Finally, the activated carbon powder was sieved through a sieve with a mesh size of 80 to 325 to obtain a suitable activated carbon powder for later use.
[0059] Continue reading Figure 1 As shown, in the S2 mixing stage, zeolite powder, dolomite powder, spodumene powder, lithium mica powder, activated carbon powder, and adhesive are mixed and stirred in proportion to obtain a prefabricated mixture. Among them, the adhesive can be selected from at least one of polyolefins, sodium carboxymethyl cellulose, polyethylene, polypropylene, ethylene-vinyl acetate copolymer, melamine resin, and acrylic glue. Preferably, the adhesive is polyethylene or acrylic glue, which has good chemical stability and can withstand the corrosion of most acids and alkalis.
[0060] It should be noted that, according to practical applications, those skilled in the art may also use a three-dimensional mixer to stir and mix the above-mentioned zeolite powder, dolomite powder, spodumene powder, lepidolite powder, activated carbon powder, and adhesive to obtain a prefabricated mixture. The stirring speed of the three-dimensional mixer is set to 70 to 160 rpm, and the stirring time is set to 30 to 180 minutes.
[0061] It should be noted that the use of a three-dimensional mixer can enable zeolite powder, dolomite powder, spodumene powder, lithium mica powder, activated carbon powder, and adhesive to be fully stirred and mixed evenly, thereby improving the balance of the filtering performance and structural strength of the prepared strontium-lithium mineralized carbon core.
[0062] like Figure 1 and Figure 4 As shown, in the S3 forming stage, three forming treatment processes are used to prepare strontium-lithium mineralized carbon cores.
[0063] The first type of molding process, such as Figure 4 As shown, the specific steps of dry extrusion for preparing strontium-lithium mineralized carbon core include:
[0064] S31, filling the prefabricated mixture into an extruder and extruding the prefabricated mixture to form a strontium-lithium mineralized carbon core, the extrusion temperature of the extruder is 115-200°C.
[0065] Specifically, the prepared premix is filled into the feed port of the screw extruder, the extrusion temperature of the screw extruder is set to 150°C, and the screw extruder directly extrude the premix to form a strontium-lithium mineralized carbon core. The strontium-lithium mineralized carbon core formed by extrusion has an outer diameter of 60 mm, an inner diameter of 40 mm, and a strontium length of 240 mm.
[0066] The second molding process, such as Figure 4 As shown, the specific steps of dry sintering for preparing strontium-lithium mineralized carbon core include:
[0067] S321, filling the prefabricated mixed material into a mold and compacting it to form a prefabricated carbon core;
[0068] S322, sending the mold with the prefabricated carbon core into a tunnel furnace sintering device for sintering, the sintering temperature is 150-230° C., and the sintering time is 0.5-2 hours;
[0069] S323, taking out the mold, cooling it, and demolding it to prepare a strontium-lithium mineralized carbon core.
[0070] Specifically, a press is used to mold the prefabricated mixture placed in a mold. The pressure of the press is 2 to 5 kilograms, and the extrusion time is 3 to 10 seconds. The size specifications of the strontium lithium mineralized carbon core formed after the press molding are as follows: an outer diameter of 60 mm, an inner diameter of 40 mm, and a length of 240 mm.
[0071] The mold with the prefabricated mixture after molding is sent to the tunnel furnace sintering equipment for sintering at a sintering temperature of 220°C and a sintering time of 1.5 hours;
[0072] After sintering, the mold is cooled to room temperature, and the strontium-lithium mineralized carbon core is taken out after demoulding.
[0073] The third type of molding process, such as Figure 4 As shown, the specific steps of wet molding for preparing strontium-lithium mineralized carbon core include:
[0074] S331, using a vacuum machine to evacuate the cavity of the mold so that the prefabricated mixed material is sucked into the mold to form a prefabricated carbon core;
[0075] S332, using an oven to dry the prefabricated carbon core to prepare the strontium-lithium mineralized carbon core, the drying temperature is 50-150° C., and the drying time is 1-5 hours.
[0076] Specifically, the prefabricated mixed material is directly sucked into the cavity of the mold under the action of vacuum negative pressure to directly form a prefabricated carbon core, wherein the prefabricated carbon core has an outer diameter of 60 mm, an inner diameter of 40 mm, and a length of 240 mm.
[0077] The prefabricated carbon core is dried in an oven to obtain a strontium-lithium mineralized carbon core, wherein the drying temperature is 150° C. and the drying time is 2 hours.
[0078] It should be noted that after the strontium-lithium mineralized carbon core prepared by the above three processes passes the inspection, it can be sent to the assembly line to assemble the end caps and annular rings and other accessories at both ends of the strontium-lithium mineralized carbon core, and finally assembled into a mineralized filter element product.
[0079] Six specific strontium-lithium mineralized carbon core embodiments are described below:
[0080] Embodiment 1
[0081] Take 5 parts of zeolite powder, 10 parts of spodumene powder, 10 parts of lepidolite powder, 5 parts of dolomite powder, 20 parts of polyethylene (molecular weight of 3 million to 7 million), and 200 parts of activated carbon powder (screened with a 100-mesh sieve), put the above materials into a mixer, stir them evenly, and obtain a prefabricated mixture.
[0082] The prefabricated mixture is subjected to the above-mentioned dry sintering process to prepare a strontium-lithium mineralized carbon core.
[0083] Embodiment 2
[0084] Take 10 parts of zeolite powder, 25 parts of spodumene powder, 25 parts of lepidolite powder, 10 parts of dolomite powder, 40 parts of polyethylene (molecular weight is 3 million to 7 million), and 400 parts of activated carbon powder (screened with a 100-mesh sieve), put the above materials into a mixer, stir them evenly, and obtain a prefabricated mixture.
[0085] The prefabricated mixture is subjected to the above-mentioned dry sintering process to prepare a strontium-lithium mineralized carbon core.
[0086] Embodiment 3
[0087] Take 10 parts of zeolite powder, 15 parts of spodumene powder, 15 parts of lepidolite powder, 10 parts of dolomite powder, 15 parts of polyethylene (molecular weight of 50,000-200,000), and 300 parts of activated carbon powder (screened with a 200-mesh sieve), put the above materials into a mixer and stir them evenly to obtain a prefabricated mixture.
[0088] The prefabricated mixture is subjected to the above-mentioned dry extrusion process to prepare a strontium-lithium mineralized carbon core.
[0089] Embodiment 4
[0090] Take 18 parts of zeolite powder, 28 parts of spodumene powder, 28 parts of lepidolite powder, 18 parts of dolomite powder, 35 parts of polyethylene (molecular weight of 50,000-200,000), and 500 parts of activated carbon powder (screened with a 200-mesh sieve), put the above materials into a mixer and stir them evenly to obtain a prefabricated mixture.
[0091] The prefabricated mixture is subjected to the above-mentioned dry extrusion process to prepare a strontium-lithium mineralized carbon core.
[0092] Embodiment 5
[0093] Take 5 parts of zeolite powder, 10 parts of spodumene powder, 10 parts of lepidolite powder, 5 parts of dolomite powder, 6 parts of acrylic glue, and 100 parts of activated carbon powder (screened using a 300-mesh sieve), put the above materials into a mixer, stir them evenly, and obtain a prefabricated mixture.
[0094] The prefabricated mixture is subjected to the above-mentioned wet molding process to prepare a strontium-lithium mineralized carbon core.
[0095] Embodiment 6
[0096] Take 10 parts of zeolite powder, 20 parts of spodumene powder, 20 parts of lepidolite powder, 10 parts of dolomite powder, 15 parts of acrylic glue, and 300 parts of activated carbon powder (screened using a 300-mesh sieve), put the above materials into a mixer, stir them evenly, and obtain a prefabricated mixture.
[0097] The prefabricated mixture is subjected to the above-mentioned wet molding process to prepare a strontium-lithium mineralized carbon core.
[0098] The specific test method of strontium-lithium mineralized carbon core is as follows: soak the strontium-lithium mineralized carbon core in clean water and let it stand for 24 hours, and measure the concentration of strontium, lithium and other elements in the clean water. According to GB8537 "National Food Safety Standard for Drinking Natural Mineral Water", if the content of strontium or lithium in the water is greater than 0.2 mg / L, it meets the requirements of mineral water. Table 1 (Unit: mg / L) Example strontium lithium Embodiment 1 0.51 0.41 Embodiment 2 0.54 0.43 Embodiment 3 0.52 0.46 Embodiment 4 0.56 0.44 Embodiment 5 0.40 0.39 Embodiment 6 0.42 0.41
[0099] According to the test results in Table 1, the concentrations of strontium and lithium elements precipitated and released by the strontium-lithium mineralized carbon core in water are high and relatively balanced, which meets the requirements of the sanitary safety evaluation specifications for drinking water transmission and distribution equipment and protective materials.
[0100] It should be noted that the above data are actual laboratory measured performance. When entrusting a third-party organization to conduct testing, it is necessary to consider the normal fluctuation range of the values and the data differences caused by different experimental standards.
[0101] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. A strontium-lithium mineralized carbon core, It is characterized in that The invention comprises the following components in parts by weight: 5-20 parts of zeolite powder, 5-20 parts of dolomite powder, 5-30 parts of spodumene powder, 5-30 parts of lepidolite powder, 100-500 parts of activated carbon powder and 5-40 parts of adhesive.
2. The strontium-lithium mineralized carbon core according to claim 1, It is characterized in that The particle size of the activated carbon powder is 80-325 meshes.
3. The strontium-lithium mineralized carbon core according to claim 1, It is characterized in that The adhesive is polyethylene or acrylic glue.
4. A method for preparing the strontium-lithium mineralized carbon core according to any one of claims 1 to 3, It is characterized in that The following steps are involved: Ore processing stage: natural zeolite, natural dolomite, natural spodumene and natural lepidolite are modified and crushed to prepare powder for use; Mixing stage: the zeolite powder, the dolomite powder, the spodumene powder, the lepidolite powder, the activated carbon powder and the adhesive are mixed and stirred in proportion to obtain a prefabricated mixture; Forming stage: preparing the strontium-lithium mineralized carbon core by using any one of dry extrusion, dry sintering or wet forming processes for the prefabricated mixture.
5. The method for preparing the strontium-lithium mineralized carbon core according to claim 4, It is characterized in that In the ore processing stage, the specific preparation steps of the zeolite powder or the dolomite powder include: crushing the natural zeolite or the natural dolomite into crushed stone pieces with a particle size of 1 to 3 cm; Using clean water to wash the natural zeolite or the natural dolomite and then drying it; Using silicon-containing steam to perform fumigation activation modification treatment on the natural zeolite or the natural dolomite; The modified natural zeolite or natural dolomite is crushed, ground, sieved, and then the powder is taken out for later use.
6. The method for preparing the strontium-lithium mineralized carbon core according to claim 5, It is characterized in that In the ore processing stage, the specific preparation steps of the spodumene powder or the lepidolite powder include: Crushing the natural spodumene or the natural lepidolite into gravel pieces with a particle size of 1 to 3 cm; Using clean water to wash the natural spodumene or the natural lepidolite and perform drying treatment; Calcine the dried natural spodumene or natural lepidolite at a temperature of 1000 to 1200° C. for 0.5 to 2 hours; The calcined natural spodumene or natural lepidolite is crushed, ground, sieved, and then the powder is taken out for later use.
7. The method for preparing the strontium-lithium mineralized carbon core according to claim 4, It is characterized in that The specific processing steps of the activated carbon powder include: Putting coconut shell charcoal powder into a container and adding 1% to 3% hydrochloric acid or sulfuric acid solution, soaking the coconut shell charcoal powder in the solution for at least 1 hour; Rinse the coconut shell charcoal powder with clean water; The washed coconut shell carbon powder is dried and sieved to obtain the activated carbon powder.
8. The method for preparing the strontium-lithium mineralized carbon core according to claim 4, It is characterized in that The specific steps of the dry extrusion include: The pre-mixed material is filled into an extruder and extruded to form the strontium-lithium mineralized carbon core. The extrusion temperature of the extruder is 115-200°C.
9. The method for preparing the strontium-lithium mineralized carbon core according to claim 4, It is characterized in that The specific steps of the dry sintering include: Filling the prefabricated mixed material into a mold and compacting it to form a prefabricated carbon core; The mold with the prefabricated carbon core is sent into a tunnel furnace sintering device for sintering at a sintering temperature of 150 to 230° C. for a sintering time of 0.5 to 2 hours; The mold is taken out, cooled and demoulded to prepare the strontium-lithium mineralized carbon core.
10. The method for preparing the strontium-lithium mineralized carbon core according to claim 4, It is characterized in that The specific steps of the wet forming process include: Using a vacuum machine to evacuate the cavity of the mold so that the prefabricated mixed material is sucked into the mold to form a prefabricated carbon core; The prefabricated carbon core is dried in an oven to prepare the strontium-lithium mineralized carbon core, the drying temperature is 50-150° C., and the drying time is 1-5 hours.
